SCREENING AND MOLECULAR DOCKING STUDIES OF NEW NATURAL AGONISTS AGAINST PEROXISOME PROLIFERATOR-ACTIVATED RECEPTOR-ALPHA TARGETED TO TREAT OBESITY - Veeramachaneni, Ganesh Kumar; Raj K, Kranthi; Js, Bondili; Talluri, Venkateswara Rao (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Obesity was considered as a serious health concern apart from the age group in today's population globally. The percentage of obese people in the world's population is increasing at a faster rate, and health issues arising due to obesity are gradually increasing. Our present insilico study was aimed to screen out natural molecules against the peroxisome proliferator-activated receptor (PPAR), especially alpha aids in triggering the obesity. Methods: Several targets for treating obesity were identified, and one among such promising target was PPAR. Using the insilico applications such as natural database was screened and the molecules were further evaluated based on their docking score parameter with the receptor. Results: The docking methodology suggested that two molecules zinc02091671 and zinc02137525 were found to reproduce the similar type of interactions such as that of the known inhibitor and crystal ligand. Conclusion: The reported two molecules were found to be promising agonists based on the computational studies and can be advanced the in vitro based evaluation. Keywords: Obesity, Peroxisome proliferator-activated receptor, e-pharmacophore, QikProp, Docking.